Diversity and Community Structure of Butterly in Teijsmann and Soedjana Kassan Park, Bogor Botanical Garden - Rizkawati, Vina; Asmara, Yustika Tri; Khairiyyah, Anisah; Perdani, Nindyra Karimah; Fitriasari, Sheryl; Savira, Ananda Nuri; Pasaribu, Pinta Omas; Asharo, Rizal Koen; Priambodo, Rizky (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
As a megadiversity country, Indonesia is home to a large number of flora and fauna, one of which is the butterfly. The Bogor Botanical Garden, situated at the center of Bogor City, not only serves as a green open space but also as a conservation area for plants and animals composed in it.  This study aimed to assess the diversity of butterfly species in Teijsmann Park and Soedjana Kassan Park, Bogor Botanical Garden through inventory and identification.  Sampling was carried out at spots that were 100 meters apart from each other on a walked-line transect defined at the two parks. The diversity parameters assessed and analyzed are relative abundance, relative frequency, Shannon-Wiener (H’) diversity index, Evenness index (E), and dominance.  In a total of 202 sample individuals, there were identified 38 species of butterflies belonging to 5 families namely Papilionidae, Pieridae, Nymphalidae, Lycaenidae, and Hesperiidae. The highest abundance found in Teijsmann Park is Ypthima philomela from the Nymphalidae family and Zizina otis from the Lycaenidae family. Species with the highest frequency are Junonia hedonia and Ypthima philomela from the Nymphalidae family. On the other hand, the highest frequency and abundance found in Soedjana Kassan Park was Leptosia nina from the Pieridae family. Teijsmann Park showed a slightly higher value of diversity and evenness indexes (H'=2.62, E=0.84) when compared to Soedjana Kassan Park (H'=2.50, E=0.76).